Effect of Oestrus Synchronization and Method of Breeding on Oestrus Duration in Tellicherry Goats - SELVARAJU, M; KATHIRESAN, D; PATTABIRAMAN, S R (The Indian Journal of Animal Reproduction, 2023)
Oestrus was synchronized in 40 Tellicherry goats by treating intravaginally for 18 days with · Fluorogestone acetate (FGA) or Medroxy Progesterone acetate (MAP) or controlled Internal Drug Release Device (CIDR) in combination with 600 I.U. Pregnant Mare Serum Gonadotrophin at pessary withdrawal. Twelve goats observed in natural oestrum were used as control. Each treatment and control groups were divided equally into N.S. and A.I. groups. At 48 and 60 hours of pessary removal N.S. groups were bred with intact bucks and A.I. groups were artificially inseminated with frozen semen. In control group, natural service or A.I. was done twice at an interval of 12 hours after the onset of oestrum. Duration of oestrum in each doe was measured by using an apronized · buck. Overall oestrus duration was significantly higher in MAP group than other treatment and control groups. N.S. group of all treatment and control groups had uniformly shorter oestrus duration than the A.I. group. Hence, it is concluded that both MAP and natural service had influence on oestrus duration in Tellicherry Goats.